Hubungan antara Tingkat Pengetahuan dan Sosial Budaya dengan Sikap Remaja terkait Pendewasaan Usia Perkawinan - Fitria Ma'arif (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
In Indonesia, there are still many couples who married first at a young age and not in accordance with health policy. The desire to maturing age of marriage can be hampered because of low knowledge about impact of marriage in young age and number of young marriage around adolescents. The aims of this survey was to analyzed the correlation among knowledge and social culture with attitudes related to maturation age of marriage. This study use an observational research with crossectional design. This research was conducted in Tri karya high school on 9th September 2017 and used 37 students as sample. Technique of sampling used simple random sampling. Questionnaires is used to obtained the data and chi square test is used to analyzed research data. The level of knowledge, cultural and adolescent attitudes related to maturing age of marriage are variables in this study. The result of chi square test between knowledge level and adolescent attitude showed no significant relationship (p = 0.155 > α, α = 0.05). Analysis of the relationship between social culture with adolescent attitudes has significant relationship (p = 0.002 < α, α = 0.05). The conclusion in this research is knowledge level hasn’t significant correlation with adolescent attitude. Culture has a significant relationship with adolescent attitudes. An understanding about the ideal age for marriage need to be given by parents to their children. Primary Health Center can create Integrated Service for teens and socialization about maturation age of marriage can be done through it.